2010
DOI: 10.1007/s11136-010-9642-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting physical quality of life among a multiethnic sample of breast cancer survivors

Abstract: Our findings revealed ethnic variability in the associations among the individual- and systemic-level contexts influencing PQOL based on the Contextual Model of HRQOL. HRQOL research including studies examining physical outcomes can utilize a comprehensive and integrated conceptual approach that includes psychological, socio-ecological, and cultural aspects to deepen our understanding and advance the translational utility of the research into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 94 publications
(100 reference statements)
3
52
0
Order By: Relevance
“…Although there are previous findings on differences in HRQoL determinants between European, Latino, African American and Asian American patients [46], [47], this is the first study to document an even more ‘fine’ ethnic variation among three Asian ethnic groups: Chinese, Indian and Malay. Using comprehensive multivariate modeling to test both main and interaction effects, we were able to show that the effect of specific factors within each cluster of variables varied as function of ethnicity.…”
Section: Discussionmentioning
confidence: 62%
“…Although there are previous findings on differences in HRQoL determinants between European, Latino, African American and Asian American patients [46], [47], this is the first study to document an even more ‘fine’ ethnic variation among three Asian ethnic groups: Chinese, Indian and Malay. Using comprehensive multivariate modeling to test both main and interaction effects, we were able to show that the effect of specific factors within each cluster of variables varied as function of ethnicity.…”
Section: Discussionmentioning
confidence: 62%
“…Having difficulties in medical encounters may increase unmet needs pertaining to physical problems (e.g., treatment side effects) and subsequently increase physical and emotional distress[20,22-28]. Despite an increase in research on ethnic variability in QoL among BCS[29-34], studies that include Asian Americans are scarce[35,36]. …”
Section: Goalsmentioning
confidence: 99%
“…For example, Asian American breast cancer survivors have reported lower QOL than their European counterparts [9, 10]; Chinese American survivors are more likely to experience poorer socioeconomic well-being than non-Hispanic White survivors [11]. Qualitative evidence has also shown that Chinese survivors describe more distress than Americans [12].…”
Section: Introductionmentioning
confidence: 99%